On Optimal Trajectory in Space Flight - Orlov, S. (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2016)
Are investigated a trajectory of new type in distant, space flights unlike usual trajectories of direct flight to heavenly object (Moon) it is supposed to use asymmetry of a gravitational field and to carry out flight bypassing the most power gravitational impact on the spacecraft. It leads to economy of power for 20-30 %.